Influence of surface tension and inner pressure on the process of fibre drawing - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (Journal of Lightwave Technology, 2010)
The present contribution deals with thermofluidynamical features occurring during the drawing of capillaries for microstructured optical fibres. Here, the process stability depends strongly on flow and thermal processes taking place as a preform is heated and drawn in the furnace. This is the case particularly for hollow fibres for which the existence of the inner hole directly depends on material parameters such as the surface tension and the rheological properties and on process parameter such as hole internal pressure and the process temperature. A fluid-mechanics model suggested in the literature that makes use of asymptotic analysis based on small aspect ratio of the micro capillaries, has been revisited and improved recently and the leading-order equations have been then examined in some asymptotic limits by Luzi et al.. Starting from the novel class of solutions of the simplified equations of motion the present paper focuses on the effect of both surface tension and internal hole pressure since those are of essential importance during drawing. Thus, comparisons with experimental data are performed, in order to validate the analytical model developed in , which will be briefly presented here. The theoretical model gives very accurate predictions both when the internal hole is pressurized or when no pressure is applied, as long as the temperature does not reach too high values. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.influe
Keywords: Asymptotic analysis; Holey fibres; Micro structured optical fibres (MOFs); Numerical methods; Photonic crystal fibres